ECOLOGICAL AND IDEOLOGICAL REPRESENTATION OF KABHANTI PERFORMED BY MUNA COMMUNITY IN MUNA REGENCY, SOUTH EAST SULAWESI - -, Hadirman (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2013)
Kabhanti is one of the oral traditions performed by Muna community. It is performed as part of the traditional ceremony adhered to by Muna community as an amusement and a means of presenting ideas and ideologies, and bequeathing the values which are useful to human life. Specifically, this present study was intended to describe the forms of ecological representation of Kabhanti performed by Muna community, to reveal the ideology it contains, and to interpret the ecological meanings it contains. The theory of ecolingistics, the theory of ideology, and the theory of semiotics were eclectically used in the present study. Qualitative method was used and the data were descriptively and interpretatively analyzed. The present study was conducted at Watumela Village and Latugho Village, Lawa District, Muna Regency. The data were collected through participatory observation, in-depth interview, the informants’ personal experience, and documentary study. The results of the study showed that ecologically the kabhanti performed by Muna community represented natural environment and human environment. All the ecological lexical items and the human ecological lexical items in such a performance reflected the existence of Muna people in their lives. It contained environmental, educational, social and developmental ideologies. The meanings of ecological representation in this present study included the meaning of environment, the meaning of cultural endurance, the meaning of identity, and the meaning of solidarity.